‘Vote the Assholes Out’: How Value Congruence Work Aligns Stakeholders for Corporate Activism - Buchanan, Sean; Mohammadnejad Shourkaei, Mojtaba; Dyck, Bruno (Journal of Management Studies, 2025)
Recent research has pointed to value congruence between a firm and its stakeholders as a key driver of corporate socio‐political activism. However, this ‘stakeholder alignment’ model of corporate activism does not adequately explain how firms foster value congruence with their stakeholders. Drawing from an inductive study of Patagonia, Inc., we develop a social‐symbolic work perspective of stakeholder alignment for corporate activism by introducing the concept of ‘value congruence work’. Our findings demonstrate how attractional value congruence work aims to draw in stakeholders with similar values to engage with the firm, and co‐evolutionary value congruence work facilitates different forms of learning to sustain alignment between a firm and its stakeholders. Our findings offer new insights for research on corporate socio‐political activism and values work in organizations.